Mirror Visual Feedback-Induced Performance Improvement and the Influence of Hand Dominance - Rjosk, Viola; Kaminski, Elisabeth; Hoff, Maike; Sehm, Bernhard; Steele, Christopher J.; Villringer, Arno; Ragert, Patrick (Frontiers in Human Neuroscience, 2016)
Mirror Visual Feedback (MVF) is a promising technique in clinical settings that can be used to augment performance of an untrained limb. Several studies with healthy volunteers and patients using transcranial magnetic stimulation (TMS) or functional magnetic resonance imaging (fMRI) indicate that functional alterations within primary motor cortex (M1) might be one candidate mechanism that could explain MVF-induced changes in behavior. Until now, most studies have used MVF to improve performance of the non-dominant hand. The question remains if the behavioural effect of MVF differs according to hand dominance. Here, we conducted a study with two groups of young, healthy right-handed volunteers who performed a complex ball-rotation task while receiving MVF of the dominant (n = 16, group 1, MVFDH) or non-dominant hand (n = 16, group 2, MVFNDH). We found no significant differences in baseline performance of the untrained hand between groups before MVF was applied. Furthermore, there was no significant difference in the amount of performance improvement between MVFDH and MVFNDH indicating that the outcome of MVF seems not to be influenced by hand dominance. Thus our findings might have important implications in neurorehabilitation suggesting that patients suffering from unilateral motor impairments might benefit from MVF regardless of the dominance of the affected limb.